2020
DOI: 10.1016/j.jcv.2020.104387
|View full text |Cite
|
Sign up to set email alerts
|

Detection of low levels of SARS-CoV-2 RNA from nasopharyngeal swabs using three commercial molecular assays

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 6 publications
4
29
0
Order By: Relevance
“…Though tempting, this cannot be interpreted as an 8.6-13.0 times less sensitivity based on this Ct-difference alone (calculated with 100% PCR reaction efficiency), since in samples with a relatively low SARS-CoV-2 RNA load, the difference in Ct-value between the cobas®6800 assay targets and LDA tended to be much lower. This effect confirmed observations in a previous study [ 10 ]. The difference in Ct-values between the cobas®6800 and LDA targets was higher in lower respiratory specimens, with no significant effects on qualitative results in this sample type.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Though tempting, this cannot be interpreted as an 8.6-13.0 times less sensitivity based on this Ct-difference alone (calculated with 100% PCR reaction efficiency), since in samples with a relatively low SARS-CoV-2 RNA load, the difference in Ct-value between the cobas®6800 assay targets and LDA tended to be much lower. This effect confirmed observations in a previous study [ 10 ]. The difference in Ct-values between the cobas®6800 and LDA targets was higher in lower respiratory specimens, with no significant effects on qualitative results in this sample type.…”
Section: Discussionsupporting
confidence: 93%
“…Widespread laboratory testing of potentially infected patients has a central role in attempts to mitigate the spread of SARS-CoV-2 [ 5 ], and requires rapid upscaling of the test capacity by automation [ 6 , 7 , 8 ]. Several automated systems, like the cobas®6800 assay, have been validated for the detection of SARS-CoV-2 in oro-/nasopharyngeal swabs in virus transport medium [ [9] , [10] , [11] ], but performance data for other clinical specimen types are limited. Several studies involving SARS-CoV-2 detection using PCR assays use samples which have undergone a freeze-thaw cycle [ 9 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a multicenter evaluation of that assay showed no cross-reactivity with other respiratory pathogens, including human coronaviruses ( Loeffelholz et al (2020) ). Recent reports describe performance differences between the cobas® and Xpert® systems for samples that contain low levels of target ( Lowe et al, 2020 ; Moran et al, 2020 ). The majority (75 %) of our clinical specimens were strong positives (LDT-1 C t ≤ 30) and only two samples had C t values >35.…”
Section: Discussionmentioning
confidence: 99%
“…Another POC diagnostic that received the FDA's EUA is the Accula SARS-CoV-2 test, a handheld device that also uses PCR technology to detect SARS-CoV-2 in throat and nasal swab specimens. Specimens are added to a buffer to solubilize the samples 30,31 One study (comparing Xpert Xpress, ID NOW, and the ePlex systems) found that although all 3 had 100% specificity (did not exhibit false-positive results), Xpert Xpress performed well and had the lowest limit of detection and highest sensitivity, whereas the ePlex and ID NOW had lower sensitivities. 32 Another study determined that the POC test (ID NOW) was less sensitive compared with the traditional RT-PCR assay.…”
Section: Assay Performance and Limitationsmentioning
confidence: 99%